Mapping the trends of sustainable supply chain management research: a bibliometric analysis of peer-reviewed articles - Amofa, Birago; Oke, Adekunle; Morrison, Zoe (Frontiers in Sustainability, 2023)
This bibliometric analysis explores the scope and knowledge base of scholarly efforts on sustainable supply chain management (SSCM) and how it has evolved in different economies and businesses to advance circular economy (CE) discourses in theory and practice across economies and businesses. Using the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines and search syntax, a total of 2,574 peer-reviewed articles from journals indexed in Web of Science, Scopus, and ProQuest were analyzed. The results show an exponential growth in SSCM research since 2013 with 6,306 authors from 83 countries published in 675 journals; however, less attention is given to developing economies (DEs) and Micro, Small and Medium Enterprises (MSMEs). The findings provide a useful direction for future research and theory development in SSCM, allowing scholars and businesses to implement true CE by addressing practical sustainability issues relevant to their operations and supply chains. This bibliometric analysis is the first study providing a holistic overview of SSCM research trends in developed countries (DCs), DEs, and MSMEs, and arguing for inter-disciplinary CE discourses and inter-organizational collaboration in SC to update and implement CE. This study makes important contributions to SSCM research and practice by providing multiple snapshots of the increasing growth trajectory of the idea of sustainability in SC and how its different aspects have evolved over the period.